2020
DOI: 10.1042/bcj20190740
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase CK2 phosphorylation of SAPS3 subunit increases PP6 phosphatase activity with Aurora A kinase

Abstract: Protein Ser/Thr phosphatase-6 (PP6) regulates pathways for activation of NF-kB, YAP1 and Aurora A kinase (AURKA). PP6 is a heterotrimer comprised of a catalytic subunit, one of three different SAPS subunits and one of three different ankyrin-repeat ANKRD subunits. Here, we show FLAG-PP6C expressed in cells preferentially binds endogenous SAPS3, and the complex is active with the chemical substrate DiFMUP. SAPS3 has multiple acidic sequence motifs recognized by protein kinase CK2 (CK2) and SAPS3 is phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…We found that MEK1 co-immunoprecipitated with each of the PP6 regulatory subunits (Figure 5D), with Article ll OPEN ACCESS significantly less associating with FLAG-tagged PPP6C. These results suggest that PP6 regulatory subunits serve to recruit MEK to the PP6 complex for dephosphorylation by PPP6C, consistent with a general role for non-catalytic subunits of PP6 and other PP2A family phosphatases in substrate binding (Brautigan and Shenolikar, 2018;Heo et al, 2020;Hosing et al, 2012;Stefansson and Brautigan, 2006;Zhong et al, 2011). In keeping with our observation that MEK binds to each of the regulatory subunits, we found that combined siRNA silencing of PPP6R1, PPP6R2, and PPP6R3, but not knockdown of individual subunits, significantly elevated MEK phosphorylation in 501mel cells (Figure S5D).…”
Section: Figure 2 Ppp6c Negatively Regulates Erk Signalingsupporting
confidence: 63%
See 2 more Smart Citations
“…We found that MEK1 co-immunoprecipitated with each of the PP6 regulatory subunits (Figure 5D), with Article ll OPEN ACCESS significantly less associating with FLAG-tagged PPP6C. These results suggest that PP6 regulatory subunits serve to recruit MEK to the PP6 complex for dephosphorylation by PPP6C, consistent with a general role for non-catalytic subunits of PP6 and other PP2A family phosphatases in substrate binding (Brautigan and Shenolikar, 2018;Heo et al, 2020;Hosing et al, 2012;Stefansson and Brautigan, 2006;Zhong et al, 2011). In keeping with our observation that MEK binds to each of the regulatory subunits, we found that combined siRNA silencing of PPP6R1, PPP6R2, and PPP6R3, but not knockdown of individual subunits, significantly elevated MEK phosphorylation in 501mel cells (Figure S5D).…”
Section: Figure 2 Ppp6c Negatively Regulates Erk Signalingsupporting
confidence: 63%
“…While we did not observe changes in levels of PPP6C upon inhibition of BRAF-MEK-ERK signaling, we cannot rule out transcriptional control of PP6 regulatory or scaffolding subunits as a mechanism of feedback regulation. Furthermore, because phosphorylation of PP6 regulatory subunits can mediate recruitment to substrates and other interaction partners (Heo et al, 2020;Kettenbach et al, 2018), targeting of MEK may be impacted by ERK-dependent phosphorylation or other modifications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significantly less MEK1 associated with FLAG-tagged PPP6C. These results suggest that PP6 regulatory subunits serve to recruit MEK to the PP6 complex for dephosphorylation by PPP6C, consistent with a general role for non-catalytic subunits of PP6 and other PP2A family phosphatases in substrate binding (Brautigan and Shenolikar, 2018; Heo et al, 2020; Hosing et al, 2012; Stefansson and Brautigan, 2006; Zhong et al, 2011).…”
Section: Resultssupporting
confidence: 55%
“…1E), a ubiquitin ligase involved in DNA double strand break repair (34), and PP6R3/SAPS3 ( Fig. 1F), a regulatory subunit of protein phosphatase 6 (35).…”
Section: Tulp3 Interacts With a Diverse Set Of Cytoplasmic And Nucleamentioning
confidence: 99%